Epidemiological profile of deaths from cystic fibrosis in Brazil between 2012 and 2022 based on data from the repository of the Department of Information Technology of the Unified Health System (DataSUS) (Research, Society and Development, 2024)
Introduction: Cystic fibrosis is an autosomal recessive hereditary disease that mainly affects the respiratory system and gastrointestinal tract, and those with this comorbidity may die due to its complications. Objective: This study aims to describe the epidemiological characteristics of deaths from cystic fibrosis in Brazil between 2012 and 2022. Methodology: This is a cross-sectional study, in which the researchers analyzed data available in the Mortality Information System (SIM), of the Department of Information Technology of the Unified Health System (DataSUS). Results: According to the variables investigated, the results found point to the year 2022 with the highest percentage of deaths due to cystic fibrosis with 11.99% (n = 291), a higher prevalence of females, representing 50.87% (n = 1,234), in the age group of 80 years or older, with 16.24% (n = 394), white, with 59.73% (n = 1,449), and the Southeast Region and city of São Paulo, presenting 43.56% (n = 1,057) and 22.63% (n = 549) of total deaths, respectively. Conclusion: Thus, we highlight the importance of encouraging the expansion of health policies for the treatment of individuals with cystic fibrosis, aiming to reduce the number of deaths from this disease in Brazil.